Choice Theory and Reality Therapy to Prevent Sexual Misconduct among Youth: A Current Review of Literature - Izzah Supeni; Ahmad Jazimin Jusoh (International Journal of Education, Information Technology, and Others, 2021)
Choice Theory and Reality Therapy (CTRT) has been used widely in educational context to stimulate students` behaviors by giving them freedom and responsibility to make a valuable decision for their lives. This study aims to identify some relevant current literatures related to CTRT to prevent sexual misconduct among youth. The methodology used in this study is qualitative by using literature approach in searching, selecting, analyzing, and reporting several previous research studies. The study shows that the implementation of five basic needs, namely: survival, love and belonging, power, freedom, and fun in CTRT may help to prevent sexual misconduct among the youth. This study recommends for further study that it should be created a CTRT module for preventing sexual misconduct that can be used by school counsellors and practitioners for helping young generation to gain their normal life among their communities` members.